Enhancement of starch production in tobacco through transfer of the gene encoding bacterial ADP glucose pyrophosphorylase - Ngọc, Lê Thu; Hưng, Nguyễn Mậu; Hùng, Đinh Văn; Hồng, Nguyễn Thị Minh; Ngọc, Phạm Bích; Hà, Chu Hoàng (Vietnam Journal of Biotechnology, 2016)
Starch is the primary storage polysaccharide in plants.  It not only plays a role as the most important nutritional component in the diet of humans and many animal species, but is also a raw material in the food processing industry or material industry. Therefore, a current research direction is the improvement of crops by increasing starch yields based on enhancing the activity of key enzymes involved in starch biosynthesis by genetic engineering. ADP-Glc pyrophosphorylase (AGPase) is an important regulatory enzyme for synthesis of glycogen in bacteria and starch in plants. In this paper, the 1.5 kb synthetic mutant of AGPopt gene derived from E. coli AGPase was inserted into the plant expression vector pBI121 under the control of 35S promoter. The efficiency of this construct was tested in transgenic Nicotiana tabacum. The integration of AGPopt into the plant genome was confirmed by PCR and Southern hybridization, and the expression of bacterial AGPase in transgenic lines was detected by Western hybridization. Interestingly, starch assays in 7 tobacco transgenic lines resulted in 5 lines displaying an increase in the levels of starch accumulated in the leaves, approximately 18%–56% higher than those of WT plants. These results indicate that the expression of AGPopt is one of effective strategies for enhanced starch production in plant.